Supercritical Impregnation and Kinetic Release of 2-Nonanone in Lldpe Films Used for Active Food Packaging - Guarda-Moraga, A; Romero-Figueroa, J; Galotto-Lopez, M; Rojas-Sepulveda, A; Torres-Mediano, A; Cerro-Munoz, D (Elsevier B.V., 2015)
The impregnation of active compounds in polymeric matrices using supercritical carbon dioxide (scCO2) is a well-known technique, which is currently used to formulate controlled drug release materials. In this study, supercritical impregnation of 2-nonanone in linear low-density polyethylene (LLDPE) was done in order to prepare active polymer films to be used in food packaging. Impregnation tests were carried out in a high-pressure cell, at 313 K with pressures ranging from 12 to 22 MPa and at two different depressurization rates: 1.0 and 10.0 MPa min−1. This procedure allowed the preparation of films containing 2-nonanone at concentrations varying from 0.21 to 0.34 w/w%. Higher concentrations of 2-nonanone in LLDPE were obtained for impregnations done at lower pressures and the lowest depressurization rate. Release experiments showed that the depressurization rate of the impregnation process is a key parameter, which significantly affects the initial content of the active compound in the polymer. Simultaneously, a phenomenological mass transfer model has been used to describe the release of 2-nonanone from the polymer to a food simulant. This model was used to correlate the experimental release kinetic data, obtaining the values of diffusion coefficient of 2-nonanone in LLDPE, which were quantified between 3.0 × 10−12 and 3.6 × 10−12 m2 s−1 when depressurization rate was 10.0 MPa min−1 and 6.8 × 10−12 m2 s−1 when its value was 1.0 MPa min−1. © 2015 Elsevier B.V.